2004
DOI: 10.1152/jn.00059.2004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Improves Response Strength, Threshold, Selectivity, and Latency of Auditory Cortex Neurons

Abstract: Environmental enrichment improves response strength, threshold, selectivity, and latency of auditory cortex neurons. J Neurophysiol 92: 73-82, 2004. First published March 10, 2004 10.1152/jn.00059. 2004. Over the last 50 yr, environmental enrichment has been shown to generate more than a dozen changes in brain anatomy. The consequences of these physical changes on information processing have not been well studied. In this study, rats were housed in enriched or standard conditions either prior to or after reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
133
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(157 citation statements)
references
References 56 publications
17
133
1
6
Order By: Relevance
“…Our findings of auditory brain plasticity before full gestation are in keeping with several studies, primarily by Merzenich and colleagues, showing that early auditory experience, either in the form of enrichment or impoverishment, can have a substantial impact on both the structural and functional development of the AC in rat pups (26,27,29,31,57,58). Similarly, an established body of work by Lickliter and colleagues has shown that bobwhite quail chicks receiving auditory stimulation early in embryogenesis demonstrated improved auditory learning and memory when tested postnatally (59)(60)(61).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings of auditory brain plasticity before full gestation are in keeping with several studies, primarily by Merzenich and colleagues, showing that early auditory experience, either in the form of enrichment or impoverishment, can have a substantial impact on both the structural and functional development of the AC in rat pups (26,27,29,31,57,58). Similarly, an established body of work by Lickliter and colleagues has shown that bobwhite quail chicks receiving auditory stimulation early in embryogenesis demonstrated improved auditory learning and memory when tested postnatally (59)(60)(61).…”
Section: Discussionsupporting
confidence: 91%
“…Numerous animal studies have shown that brain development relies on developmentally appropriate acoustic stimulation early in life (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Auditory deprivation during critical periods can adversely affect brain maturation and lead to long-lasting neural despecialization in the auditory cortex (AC), whereas auditory enrichment in the early postnatal period can enhance neural sensitivity in the primary AC, as well as improve auditory recognition and discrimination abilities.…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that altered sensory experience can reorganize cortical responses (Ahissar et al, 1992;Edeline, 1999;Engineer et al, 2004). Significant changes have been observed in receptive field size, cortical topography, response latency, spectrotemporal selectivity, response strength, and neuronal discharge coherence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, explicit exposure to particular sound frequencies can enhance the number of cortical neurons driven by those stimuli and alter neuronal tuning properties and response latencies to favor behaviorally relevant sounds [19]. Environmental enrichment can also sharpen neuronal tuning curves in auditory cortex [20], while noisy environments impair the development of normal tuning [21].…”
Section: Cortical Plasticity and Perceptual Learningmentioning
confidence: 99%